Platelet-activating factor: an inflammatory mediator in the acute phase of allergic conjunctivitis in a guinea-pig model - F. Meijer; J. L. van Delft; N. J. van Haeringen (Mediators of Inflammation)
The role of platelet-activating factor (PAF) as a mediator of increased conjunctival vascular permeability was investigated in a guinea-pig model of immediate hypersensitivity. Vascular permeability of the conjunctiva was determined by measuring the albumin content in lavage fluid (LF) after topical challenge with either PAF or ovalbumin. PAF produced a dose-dependent increase of the vascular permeability within minutes. Topical pretreatment with levocabastine, a potent histamine H1-antagonist demonstrated no effect towards the vascular permeability in response to PAF provocation. Pretreatment with eyedrops containing the specific PAF antagonist BN 52021 (1%) showed a significant inhibition of the vascular permeability (60.2%) and the clinical score (27.5%) after PAF challenge. In sensitized guinea-pigs, levocabastine showed a marked inhibition of both the vascular permeability (80.5%) and the clinical score (70%) after topical challenge with ovalbumin. BN 2021, although to a lesser extent, showed a similar effect towards the vascular permeability (26.8%) and the clinical score (28%) after antigen provocation. When BN 52021 and levocabastine were administered in combination, the vascular permeability was significantly decreased after antigen challenge in comparison with eyes pretreated with levocabastine alone. These results indicate that PAF plays a role in the acute phase of allergic conjunctivitis in the guinea-pig.